Clustering patients by depression symptoms to predict venlafaxine ER antidepressant efficacy: Individual patient data analysis. (October 2020) - Kato, Masaki; Asami, Yuko; Wajsbrot, Dalia B.; Wang, Xuemei; Boucher, Matthieu; Prieto, Rita; Pappadopulos, Elizabeth
Abstract: Objective: To identify clusters of patients with major depressive disorder (MDD) based on the baseline 17-item Hamilton Rating Scale for Depression (HAM-D17 ) items and to evaluate the efficacy of venlafaxine extended release (VEN) vs placebo, and the potential effect of dose on efficacy, in each cluster. Methods: Cluster analysis was performed to identify clusters based on standardized HAM-D17 item scores of individual patient data at baseline from 9 double-blind, placebo-controlled studies of VEN for MDD. Change from baseline in HAM-D17 total score was analyzed using a mixed-effects model for repeated measures for each cluster; response and remission rates at week 8 were analyzed using logistic regression. Discontinuation rates were also evaluated in each cluster. Results: In 2599 patients, 3 patient clusters were identified, characterized as High modified Core (mCore) Symptoms/High Anxiety (cluster 1), High mCore Symptoms/Medium Anxiety (cluster 2), and Medium mCore Symptoms/Medium Anxiety (cluster 3). Significant effects of VEN vs placebo were observed on change from baseline in HAM-D17 total score at week 8 for both clusters 1 and 2 (both P < 0.001), but not for cluster 3. In cluster 3, a significant treatment effect of VEN was observed at week 8 in the lower-dose subgroup but not in the higher-dose subgroup. All-cause discontinuation rates were significantly higher in placebo than VEN in each cluster. Conclusions: Three unique clusters of patients were identified differing in baseline mCore symptoms and anxiety. Cluster membership may predict efficacy outcomes and contribute to dose effects in patients treated with VEN. Clinical trials registration: NCT01441440; other studies included in this analysis were conducted before the requirement to register clinical studies took effect. Highlights: Three clusters were identified for MDD, characterized as the severity of modified core-depressive symptoms and anxiety. Treatment effects of venlafaxine differed across patient clusters. Baseline symptom clusters for MDD are useful in predicting dose-dependent treatment effect of venlafaxine extended release. Further exploration of factors that may affect efficacy of venlafaxine is needed.